Globalizáció, közvetlen külföldi tõkebefektetések és a vezetői gyakorlat modernizációja - Makó, Csaba; Ellingstad, Marc (Szociológiai Szemle, 2024)
This paper has aimed to examine the various possibilities and limitations of Foreign Direct Investments (FDI) as an engine of modernization in the Hungarian Economy. The focus in our investigation was the business organization (firm) which is a core institution in reorganizing economic activities in the so-called “transformation economies” of Central and Eastern Europe (CEE). Evaluating the role played by foreign-owned firms in the technological and organizational innovations o f the host country is rather ambiguous. Empirical evidences on Research and Development (R_D) activities clearly illustrated that, until now, Multinational Corporations (MNCs), operating in the region, having the largest share of FDI in Hungary, have not become involved deeper in indigenous research or in the development of “know-why” activities. Summing up our results and with reference to other studies dealing with globalization, the CEE countries’ participation in the multi-national world production system is rather limited at this moment.